Transmission of antimicrobial resistance genes from the environment to human gut is more pronounced in colorectal cancer patients than in healthy subjects - Weixin Liu; Harry C. H. Lau; Xiao Ding; Xiaole Yin; William Ka Kei Wu; Sunny Hei Wong; Joseph J. Y. Sung; Tong Zhang; Jun Yu (iMeta)
Abstract Antimicrobial resistance is a major global health concern. However, the source of gut resistome remains unsolved. We aimed to analyze the contribution of environmental antimicrobial resistance genes (ARGs) to colorectal cancer (CRC) patients. Here, we collected metagenomic data from 1,605 human stool samples (CRC = 748; healthy = 857) and 1,035 city‐matched environmental samples, in which 110 CRC, 112 healthy, and 56 environmental samples were newly collected. Compared to healthy subjects, CRC patients had significantly higher ARG burden (p < 0.01) with increased levels of multidrug‐resistant ARGs. Gut ARGs in CRC also had a closer similarity to environmental ARGs (p < 0.001). By comparing environmental and gut ARGs, 28 environmental ARGs were identified as CRC‐specific ARGs, including SUL2 and MEXE, which were not identified in healthy subjects. Meanwhile, more mobile ARGs (mARGs) from the environment were observed in CRC patients compared to healthy subjects (p < 0.05). The hosts of mARGs were mainly pathogenic bacteria (e.g., Escherichia coli (E. coli) and Clostridium symbiosum (C. symbiosum)). Compared to healthy subjects, CRC patients showed elevated horizontal gene transfer efficiency from the environment to gut. Consistently, the abundance of pathobionts carrying specific mARGs (e.g., E. coli‐SUL2 and C. symbiosum‐SUL2) were significantly increased in CRC patients compared to healthy subjects (p < 0.05). We thus reveal a route of ARG dissemination from the environment into the gut of CRC patients.